2021
DOI: 10.5222/jarss.2021.02996
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as an Adjuvant to Lignocaine for Intravenous Regional Anesthesia for Forearm and Hand Surgeries: A Prospective, Randomized, Controlled Study

Abstract: Objective: Intravenous regional anesthesia (IVRA) is an effective anesthetic technique for surgical procedures of short duration involving the distal parts of the limbs. Intraoperative tourniquet pain is the major restraint of this technique, and to overcome this limitation, various adjuvants to local anesthetics have been used. This study investigated the effect of a fixed low dose of dexmedetomidine as an adjuvant to lignocaine on intraoperative tourniquet pain, onset of block, duration of block, and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…One-tailed alpha error was set at 0.05, power at 0.80, and effect size at 0.6 based on previous studies and the allocation ratio was set at N2/N1:1. Calculations found that the sample should include a minimum of 52 subjects [21].…”
Section: Discussionmentioning
confidence: 99%
“…One-tailed alpha error was set at 0.05, power at 0.80, and effect size at 0.6 based on previous studies and the allocation ratio was set at N2/N1:1. Calculations found that the sample should include a minimum of 52 subjects [21].…”
Section: Discussionmentioning
confidence: 99%
“…In intravenous regional anesthesia, dexmedetomidine with lignocaine accelerated onset and prolonged both sensory and motor blockade in upper limb orthopedic surgery. 17 Combining xylocaine and dexmedetomidine in Bier's block for upper limb surgery significantly prolongs analgesia (6.8…”
Section: Methodsmentioning
confidence: 99%